Pulmonary Embolism - Moser, K. M. (Hämostaseologie, 1997)
Our diagnostic approach to the embolic suspect involves a high index of suspicion based on the clinical context. Next, study of the lower extremity veins; if such a study (IPG, Duplex, venogram) discloses proximal DVT, the patient needs treatment and a search for embolism may or may not be required. If it is, perfusion and ventilation scans are performed next. If this test is non-diagnostic, pulmonary angiography is the final step. As noted, other technics are under investigation. It will take time to assess whether their promise is fulfilled since it is well-known that “early reports” are usually the most positive and may not translate into clinical, non-investigative use.